Novos valores, velhas questões: o planejamento urbano em Governador Valadares - Cristiana Maria de Oliveira Guimaraes (2009)
This thesis has as its objectives verify how determinations of Brazilian Constitution´s urban policies are assumed at Governador Valadares reality. This analysis has been realized from the argument these determinations are innovations on urban comprehension. Those innovations are supposed to build democratic and just cities. At a second time, the analysis of the local material conditions of the city became important too. In this way, we choose to run over a historical trajectory about Governador Valadares urban development. Around these purposes, we analyzed the most principals Governador Valadares plans and their results, which were compared with the local legislation in three different moments, with emphasis at the last one, which corresponds to Brazilian constitution of 1988.